Referência e contrarreferência na especialidade de endodontia em um Centro de Especialidade Odontológicas - Maria Beatriz Pires de Magalhaes (2017)
The aim of this study was to know the itinerary of patients treated in primary care and referred to endodontics at Center of Dental Specialties (DSC) in Belo Horizonte, MG and the outcome of their treatment. This was a cross-sectional study which data collect used two forms: (1) about the endodontic treatment, filled by endodontists; and (2) data from the medical records of restorative treatment collected by researchers. The results were analyzed by frequency and percentiles using the SPSS 19.0 program. A total of 452 endodontic treatments were completed from May to November 2016. Patients presented a median of 39 years old, the majority were female (69.7%) and presented a primary care (PC) reference form (96.2%). Most of the endodontic treatments were performed in upper premolars (23.7%) followed by lower molars (22.3%), using a mixed technique (74.1%) and in a single session (64.2%). The referral for restorative treatment was to the DSC in 81.2% and to PC in 18.8% of the cases, and was completed in 24.1% of the cases. Of the 452 endodontic treatments finished, 109 (24.1%) had their restorative treatment completed (94 in DSC, 14 in PC and 1 in private practice), 123 (27.2%) were being treated (118 in DSC, 2 in PC and 3 in private practice), and 220 (48.7%) did not present information about the restorative treatment until the period of data collection. The restorative treatment followed the trend shown by reference, where most of the finished and ongoing treatments were or were being performed in the DSC (46.9%). It was observed that the counter-reference after the restorative treatment occurred in 58.7% of the 109 completed cases. The median waiting time for the patient to begin endodontic treatment after the PC referral for secondary care was 5 months. When considering the median time to perform endodontic treatment and for referral to restorative treatment, this was 0 days (on the same day as the single session of endodontic treatment). After the referral to the restorative treatment the patient waited a median of 57 days to be attended, and this treatment had a duration median of 17 days. It is necessary a joint planning of the dental treatment that aims to ensure the outcome of the restoration of the endodontically treated teeth and their maintenance in function, fulfilling the integrality principle.